Circumference measured at different sites of the trunk and cardiometabolic risk factors. DOI: 10.5007/1980-0037.2011v13n4p250 - Stênio Carvalho Santos; Sandra Rocha Gadelha; Rosinei Barros; Luiz Fernando Paulino Ribeiro; Viviane Valentim Alves (Revista Brasileira de Cineantropometria e Desempenho Humano, 2011)
The objectives of this study were to compare waist and abdominal circumference and to analyze their association with cardiometabolic risk factors in employees of a university in Bahia. Fifty-five men and 71 women (36.4 ± 11.2 years) were submitted to anthropometric assessment and measurement of systolic and diastolic blood pressure, blood glucose, triglycerides, total cholesterol, and HDL and LDL fractions. Despite strong correlations (P < 0.01) between the different measures (r > 0.93), waist circumference was significantly lower than abdominal circumference in the two genders, with the mean difference being greater in women (8.6 ± 4.1 vs 3.8 ± 4.2 cm; P < 0.01). Waist circumference was significantly associated with two and four risk factors in men and women, respectively. On the other hand, abdominal circumference was significantly associated with one risk factor in men and with five factors in women. No significant differences (P > 0.05) between correlation coefficients were observed in cases in which the two circumference measures were significantly associated with one risk factor. These results suggest that the site of measurement has substantial influence on circumference measured in the lower region of the trunk, particularly in women. However, there is no clear evidence of the superiority of a single measure in terms of the association with traditional cardiometabolic risk factors in the Brazilian sample studied. Further investigations are needed to compare the predictive capacity of different circumference measures for the development of risk factors and cardiovascular diseases in different populations.